PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS SMARTPHONE UNTUK SISWA KELAS I SD/MI - Muhammad Iqbal; Kartono Kartono; Siti Halidjah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe aim of this research was to develop a interactive learning media based on Adobe Flash Cs 6 for a Thematic subject. Development uses Adobe Flash Cs 6 software to produce interesting learning media equipped with animations, images, and sound. This research and development used and modificated the Borg And Gall development design model. A sample group used for this researcah was ten primary students in first level from Primary School of 24 Teluk Durian. In addiction, the apparatuses for this research consisted of a questionnaire for expert validity and response by student in content as well as techincal method. A quality evaluation result of a interactive learning media by the experts had a good value 4,55 its in a very good rate. Also, The result of research showed that an interactive learning media also had a very good value. In conclusion, this a interactive learning media for a Thematic subject had a very good quality that could be used by the first level of primary students.